Beyond Cannabidiol: The Contribution of Cannabis sativa Phytocomplex to Skin Anti-Inflammatory Activity in Human Skin Keratinocytes - Marco Fumagalli; Giulia Martinelli; Giuseppe Paladino; Nora Rossini; Umberto Ciriello; Vincenzo Nicolaci; Nicole Maranta; Carola Pozzoli; Safwa Moheb El Haddad; Elisa Sonzogni; Mario Dell’Agli; Stefano Piazza; et al. (Pharmaceuticals)
Background: Cannabis sativa L. (C. sativa) has a long history of medicinal use. Its inflorescences contain bioactive compounds like non-psychotropic cannabidiol (CBD), which is well known for its anti-inflammatory potential in skin conditions such as psoriasis, and psychotropic Δ-9-tetrahydrocannabinol (THC). Keratinocytes, the main cells in the epidermis, are crucial for regulating skin inflammation by producing mediators like IL-8 when stimulated by agents like TNFα. Methods: This study explores the anti-inflammatory effects of a standardized C. sativa extract (CSE) with 5% CBD and less than 0.2% THC in human keratinocytes challenged by TNFα. The aim of this study is to analyze the specific contributions of the main constituents of CSE to inflammatory responses in human keratinocytes by fractionating the extract and examining the effects of its individual components. Results: MTT assays showed that CSE was non-toxic to HaCaT cells up to 50 μg/mL. CSE inhibited NF-κB activity and reduced IL-8 secretion in a concentration-dependent manner, with mean IC50 values of 28.94 ± 10.40 μg/mL and 20.06 ± 2.78 μg/mL (mean ± SEM), respectively. Fractionation of CSE into four subfractions revealed that the more lipophilic fractions (A and B) were the most effective in inhibiting NF-κB, indicating that cannabinoids and cannflavins are key contributors. Pure CBD is one of the most active cannabinoids in reducing NF-κB-driven transcription (together with THC and cannabigerol), and due to its abundance in CSE, it is primarily responsible for the anti-inflammatory activity. Conclusions: This study highlights CBD’s significant role in reducing inflammation in human keratinocytes and underscores the need to consider the synergistic interactions of several molecules within C. sativa extracts for maximum efficacy. Standardized extracts are essential for reproducible results due to the variability in responses.